Global Property – Global Power - Lenkovics, Barnabás (Public Finance Quarterly, 2023)
How can the classic scientific categories be construed under the new circumstances, in global contexts? How do the global system of property and the global division of assets develop? Is there a chance for the more fair, by now global distribution and redistribution of public goods? Will the global ownership power become even more concentrated or is it divisible? Does the global property have social responsibility as well, and how may that be enforced? Are the human rights related to property and social security universal or are they territorial? Can the national state balances of social solidarity knocked over in the hope for global solidarity? The study searches the answers for these questions and tries to help in searching for the ever compelling common answers.